Unveiling Hybrid Communication: Political Strategies in Central Java and Insights from Salatiga - Tika Ifrida Takayasa; Yus Afrida (Fakultas Ilmu Sosial dan Ilmu Politik (FISIP) UIN Walisongo, 2025)
This article analyses the configuration of political communication strategies employed by legislative candidates in the local electoral context of Salatiga, a multicultural city in Central Java. Recent scholarship on local political communication in Indonesia has broadly examined campaign practices in a fragmented manner, often separating face-to-face interactions, digital media use, and social networks. Drawing on a systematic review of existing studies, this study demonstrates that local political communication operates through a hybrid strategy that integrates interpersonal communication, digital platforms, and socially embedded networks within a normative framework of Tolerance. Using McNair's political communication framework, this study argues that different communication channels perform distinct yet complementary functions. Face-to-face communication plays a central role in identity building and in gaining support by fostering trust and social legitimacy. At the same time, digital media primarily serves as an information source and tool, expanding the reach of messages, particularly among younger voters. Simultaneously, community-based networks and opinion leaders mediate political messages and align them with local social norms, thereby enhancing message acceptance. The findings further show that Salatiga's culture of tolerance functions not merely as a social backdrop but also as an active discursive boundary that shapes acceptable political narratives. This study contributes to the literature by offering an integrated theoretical model of local political communication that emphasizes the contextual orchestration of communication functions in multicultural settings.